Processing and characterization of plasticized PLA/PHB blends for biodegradable multiphase systems - I. Armentano; E. Fortunati; N. Burgos; F. Dominici; F. Luzi; S. Fiori; A. Jimenez; K. Yoon; J. Ahn; S. Kang; J. M. Kenny (eXPRESS Polymer Letters)
Blends of poly(lactic acid) (PLA) and poly(3-hydroxybutyrate) (PHB) plasticized with a lactic acid oligomer (OLA) added at three different concentrations (15, 20 and 30 wt% by weight), were prepared by an optimized extrusion process to improve the processability and mechanical properties of these biopolymers for flexible film manufacturing. Morphological, chemical, thermal, mechanical, barrier and migration properties were investigated and formulations with desired performance in eco-friendly films were selected. The efficiency of OLA as plasticizer for PLA_PHB blends was demonstrated by the significant decrease of their glass transition temperatures and a considerable improvement of their ductile properties. The measured improvements in the barrier properties are related to the higher crystallinity of the plasticized PLA_PHB blends, while the overall migration test underlined that all the proposed formulations maintained migration levels below admitted levels. The PLA_PHB blend with 30 wt% OLA was selected as the optimum formulation for food packaging, since it offered the best compromise between ductility and oxygen and water vapor barrier properties with practically no migration.